Task demands and visual context naturalness modulate gravitational expectation during ocular tracking of temporarily occluded ballistic trajectories - Sergio Delle Monache; Pietro Nastasi; Gianluca Paolocci; Francesco Scalici; Riccardo Ingrosso; Francesco Lacquaniti; Iole Indovina; Gianfranco Bosco (PLoS ONE, 2026)
When intercepting a moving object, ocular and hand movements are often associated. The neural control of both tasks is known to combine sensory information with predictive mechanisms. When interacting with free-falling targets, the brain may integrate visual signals with an internal representation of gravity, which can be recruited also in virtual settings, when contextual cues about the environment naturalness are available. This internal representation may be shared between oculomotor and manual control. At the same time, concurrent execution of hand and eye movements may alter the oculomotor performance. Here, we investigated how task demands and visual context naturalness affected the relative weighting of sensory feedback and predictive information for ocular tracking control. Participants tracked targets, either congruent with gravity or perturbed with altered gravity, which were projected on either pictorial or neutral background. To enforce prediction, targets were occluded for variable intervals. One group of participants performed only ocular tracking, while another group also intercepted the targets. In general, subjects’ ocular tracking depended on the target acceleration and the visual context. The effects of gravitational expectations were more evident for the time dependent oculomotor indexes (smooth pursuit and saccadic τ) and with the pictorial background, reinforcing the idea that recruitment of the gravity prior depends on the visual context. Instead, for post saccadic error and smooth pursuit gain no clear dissociation emerged between the effects of acceleration and velocity. Finally, participants who only tracked the target showed strong reliance on gravitational expectation early on, by displaying systematic oculomotor changes with the target acceleration since its perturbation. Instead, participants that also intercepted the target relied less on the gravity prior until the target occlusion, after which they showed oculomotor performance compatible with gravitational expectation. Thus, concurrence of ocular tracking and manual interception strongly influenced the temporal recruitment of the gravity prior.